2020
DOI: 10.4103/nmj.nmj_241_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of human immunodeficiency virus and hepatitis C virus infection among pregnant women attending antenatal care at a tertiary hospital in Abuja, Nigeria

Abstract: Context: Human Immunodeficiency Virus (HIV) and Hepatitis C Virus (HCV) co-infection in pregnant women has increased potential for Mother-to-Child Transmission risks of both viruses. The reports on the prevalence and risk factors for HIV and HCV co-infection in pregnancy are limited in Nigeria. Aim: The aim of the study is to determine the prevalence and potential risk factors for HIV and HCV infection among pregnant women in Abuja. Study Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
7
2
Order By: Relevance
“…This result is consistent with a study conducted in Kenya (3.8%) [ 34 ], Tanzania (3.9%) [ 35 ], Dawro (3.5%) [ 36 ], and Bahir Dar, Ethiopia (3.8%) [ 37 ]. Conversely, this finding was lower than studies done in Kano, Nigeria (7.9%) [ 33 ], Ghana (9.5%) [ 38 ], Angola (7.5%) [ 31 ], Solomon Islands (13.8%) [ 39 ], Deder (6.9%) [ 40 ], Arbaminch (4.3%) [ 41 ], Dessie (4.7%), Yirgalem (7.2%) [ 42 ], and southern Ethiopia (7.8%) [ 43 ]. However, it is higher than studies reported in Egypt (1.6%) [ 44 ] and Sudan (2.93%) [ 29 ].…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…This result is consistent with a study conducted in Kenya (3.8%) [ 34 ], Tanzania (3.9%) [ 35 ], Dawro (3.5%) [ 36 ], and Bahir Dar, Ethiopia (3.8%) [ 37 ]. Conversely, this finding was lower than studies done in Kano, Nigeria (7.9%) [ 33 ], Ghana (9.5%) [ 38 ], Angola (7.5%) [ 31 ], Solomon Islands (13.8%) [ 39 ], Deder (6.9%) [ 40 ], Arbaminch (4.3%) [ 41 ], Dessie (4.7%), Yirgalem (7.2%) [ 42 ], and southern Ethiopia (7.8%) [ 43 ]. However, it is higher than studies reported in Egypt (1.6%) [ 44 ] and Sudan (2.93%) [ 29 ].…”
Section: Discussioncontrasting
confidence: 70%
“…Pregnant women having a husband with a history of multiple sexual partners have 3.42 times more chance to acquire HIV infection compared to their counterparts. Studies conducted in Dessie, Ethiopia [ 21 ], Addis Ababa [ 6 ], Uganda [ 32 ], Cameroon [ 26 ], and Southwest Nigeria [ 33 ] showed that the habit of multiple sexual practices was significantly associated with the acquisition of HIV infection. This may be because husbands of pregnant women have risky sexual behavior that facilitates the acquisition of HIV both for them and for the women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, the rate of HIV/HCV coinfection in this study is higher than that of studies done in Ethiopia, which revealed a 1.3% rate (Balew et al, 2014). This 4.0% is also higher than the 0.5% for HIV/HCV coinfection among HIV-infected and HIV-naive children in Lagos (Lawal et al, 2020), the 1.7% in Northcentral, Nigeria (Durowaye et al, 2014), the 1.5% in the USA (Schuval et al, 2004), 1.0% was recorded by Aaron et al (2021) in Port Harcourt, Nigeria, the 0.16% prevalence in the southeast of Nigeria (Ikeako et al (2014), 0.5% in Anyigba (Omatola et al, 2019), 0.7% in the southeast (Diwe et al, 2013), 0.8% in Abuja (Agboghoroma & Ukaire, 2020), 0.8% in Osogbo (Oluremi et al (2021), 0.9% reported by Onyekwere and Hameed (2015) and 2.0% in Ethiopia (Deress et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…34 However, the prevalence in this current study was approximately one-third compared to what was found in another study in Nigeria, which was 13 years before this current study. 35 The finding implies that the prevalence is decreasing with increasing years in Nigeria. Nonetheless, the identified prevalence in this study was higher and even double the prevalence in another study 36 conducted in Lesotho, despite Lesotho being a country with a high burden of HIV infection among women of reproductive age.…”
Section: Discussionmentioning
confidence: 96%